A Treatable Cause of Cervical Myelopathy in a Young Female - Balagopal, Krishnan; Nadarajah, Jeyaseelan; Santhosh, Sreyas; Shams, Munavira K; Koshy, Riya Ann; Ponnachan, Pretty (Nepal Journal of Neuroscience, 2023)
Neuromyelitis Optica (NMO) or Devics Disease is an inflammatory demyelinating disorder of the central nervous system involving the neurons of the optic nerve and the spinal cord. It is seen more commonly in females and follows a relapsing clinical course in more than eighty percent of cases. The incidence of the same is rising in the Indian subcontinent. We present here a case of a young female patient presenting with features of a subacute cervical myelopathy with longitudinally extensive transverse myelitis on imaging of the spine. Investigations revealed features of Neuromyelitis Optica. She was diagnosed and treated early which led to good long term outcome